2006
DOI: 10.1007/s10926-005-9003-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Impingement Syndrome: A Systematic Review of the Effects on Functional Limitations and Return to Work

Abstract: The goal of this systematic review is to evaluate the effectiveness of different treatments for impingement syndrome and rotator cuff tear on the improvement in functional limitations and concomitant duration of sick leave. A systematic search for clinical trials or controlled studies was conducted with the following text words: should*, rotator cuff, impingement, work, sick leave, disabilit*, function*. Nineteen articles were included in this review. For functional limitations, there is strong evidence that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 46 publications
0
80
0
3
Order By: Relevance
“…SSS tedavisi ile ilgili 19 klinik çalışmayı derlemişler; ekstrakorporeal şok-dalga tedavisinin etkisiz, egzersiz ve manuel terapi kombinasyonunun sadece egzersiz tedavisine göre daha başarılı olduğunu, açık ve artroskopik akromiyoplastinin uzun dönemde egzersiz tedavisi ile eşit etkili olduğunu bulmuşlardır. 21 Haahr ve Ostergaard'ın yaptığı bir çalışmada; SSS tanısı almış 84 hasta randomize olarak artroskopik dekompresyon cerrahisi ve fizyoterapi + egzersiz grubuna ayrılmış, egzersiz olarak omuz stabilizatör ve elevatörlerine germe egzersizleri uygulanmıştır. On iki ay takipten sonra her iki grupta da CS'de anlamlı düzelme olmuş fakat gruplar arasında fark saptanmamıştır.…”
Section: Discussionunclassified
“…SSS tedavisi ile ilgili 19 klinik çalışmayı derlemişler; ekstrakorporeal şok-dalga tedavisinin etkisiz, egzersiz ve manuel terapi kombinasyonunun sadece egzersiz tedavisine göre daha başarılı olduğunu, açık ve artroskopik akromiyoplastinin uzun dönemde egzersiz tedavisi ile eşit etkili olduğunu bulmuşlardır. 21 Haahr ve Ostergaard'ın yaptığı bir çalışmada; SSS tanısı almış 84 hasta randomize olarak artroskopik dekompresyon cerrahisi ve fizyoterapi + egzersiz grubuna ayrılmış, egzersiz olarak omuz stabilizatör ve elevatörlerine germe egzersizleri uygulanmıştır. On iki ay takipten sonra her iki grupta da CS'de anlamlı düzelme olmuş fakat gruplar arasında fark saptanmamıştır.…”
Section: Discussionunclassified
“…Their results regarding laser therapy also paralleled ours in that it was more effective than placebo for AC. 14 For SIS, 2 reviews 95,96 reported that MT combined with exercise was effective. Bronfort et al 20 concluded that combining MT with medical care was beneficial, and another review 97 found evidence to suggest massage was superior to no treatment.…”
Section: Nonspecific Spmentioning
confidence: 99%
“…Our results contrasted with several reviews that reported that passive therapies such as LLLT and PEMF were not effective or that results were inconclusive for the treatment of RCs, AC, and SIS. 14,64,95,98 Additionally, 1 review determined that the evidence for MT was conflicting for the treatment of SIS and SP and that it was not more effective when compared with other interventions for AC. 97 Another review reported MT was inconclusive but favorable for RCs.…”
Section: Nonspecific Spmentioning
confidence: 99%
“…The incidence is higher in women and in people aged over 45 years (1) . The most frequent cause of shoulder pain is subacromial impingement syndrome (SIS) (2) which is caused by compression of the rotator cuff, long head of the biceps tendon, and subacromial bursa between the humerus and coracoacromial arch as a result of an intrinsic or an extrinsic mechanism (3) . Treatment of SIS is primarily conservative, including analgesic and anti-inflammatory drugs, corticosteroid injections, and occupational and physiotherapy interventions (4) .…”
Section: P Atıcı öZtürk Et Al Effectiveness Of Low-level Laser Thermentioning
confidence: 99%